PENGARUH LAYOUT PERKANTORAN TERHADAP KINERJA PEGAWAI DI SEKOLAH MENENGAH KEJURUSAN FARMASI IKASARI PEKANBARU - Nadya Erdiana; Irawati Irawati; Hasgimianti Hasgimianti; Rini Setyaningsih (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
Abstract Office layout is a condition where the employees used it in an organization, if the layout is arranged well, it will influence their performance at the school. This research is to know the influence of office layout toward employee performance and to see factors influencing both variables. It was a quantitative research using simple linear regression technique to study about office layout (X) and employee performance (Y) at Pharmacy Vocational High School of Ikasari Pekanbaru. This research aimed at knowing whether there was a significant influence of office layout toward employee performance at Pharmacy Vocational High School of Ikasari Pekanbaru. The subjects of this research were 31 employees using total sampling and the data analysis was helped with SPSS 20.00. The research findings showed that (1) employee performance level score was 84.87% and it was on very good category, (2) office layout score was 84.96% and it was on very good category, (3) there was a significant influence of office layout toward employee performance at Pharmacy Vocational High School of Ikasari Pekanbaru with 5% significant level 0.550 (0.826>0.3550). The calculation result of determination coefficient (R Square) was 0.672. It showed that the influence of office layout toward employee performance was 67.2%, and the rest 32.8% (100%-67.2%) was influenced by other variables that were not mentioned in this research. The school was expected to upgrade the office layout in order that employee performance could be better.